As possibilidades e ameaças da nova lei do agro para a política agrícola: perspectivas para além do agronegócio - Silva, Kleber Souza (2022)
This master thesis aims to analyse the Law n° 13.986/2020 know as “Lei de Agro”, it contains the possibilities and dangers that this legislation provide to Brazilian Agricultural Policy, specifically with modification created by Fundo Garantidor Solidário, the prevision of legal economic subvention to small rural proprieties, the dolarization of credit bonds and the land juridical possibility to foreign people. The general objective of this research consisted in analyse through Law Economic Analysis using the juseeconomic apparatus to unravel the timely possibilities created by legal diploma to agricultural policy to small and medium rural farmers, as well the lack in law introduced by this legislation. This text is organized in three chapters. The first chapter researched about the agricultural policy in Brazilian Federal Constitution, the rural globalization and the importance of rural credits, its history and the financing systems available. The second chapter discussed about the “Lei do Agro” and the enforcement of Private Financing Systems that attends to agribusiness necessities, the position of alterations closed by the law and the jurisdition from justice system about the rural credits. Last, in the third chapter was realized an analysis of Law 13.986 through Law Economic Analysis and its foundations, demonstrating the costs and incentives to decision of possible affected and benefected people by changes, making a diagnostic and later a prognostico of possibilities created by small and medium producers as well the juridical possibility created by the law about the transition of land for international people, and the proccess of dolarization of rural credit bonds. Finally the legal changes inserted by the Law 13.986 presented considerable transaction costs as vinculation of Exchange variation in credit titles, of necessity of judicial actions that can restrain the direct transference of land for foreign people, of necessity of rural credity subsidiated to social inequality in rural areas and the changes in “Lei do Agro” can and must be included in Government Agricultural Policy.